LD50 Acute Toxicity Test of the Anticancer Compound of Dibutyltin (IV) Bis-N-Benzyl Methyl Dithiocarbamate in White Mouse (Mus musculus) - Mukhlis Sanuddin; Vira Wulandari; Siska Nasril; Amelia Soyata; Indri Meirista; Medi Andriani (Asia Pacific Journal of Medical Toxicology, 2023)
Organotin compounds are organometallic compounds composed of one or more tin-carbon (Sn-C) bonds. Organotin compounds have been shown to have anticancer, antibacterial, and antitumor activities. Based on the several activities of the organotin group, it is hoped that the Dibutyltin (IV) Bis-N-Benzylmethyl Dithiocarbamate compound has the potential to be developed as a new drug candidate. To be a candidate for a new drug, the study was aimed to test and determine the safety level of the compound. Study to determine the LD50 value and category of toxicity of the Dibutyltin (IV) Bis-N-Benzylmethyl Dithiocarbamate compound in white mice (Mus musculus). This research is a laboratory experimental study using 40 white mice, consisting of 20 male mice and 20 female mice. The dose of the test substance was 240, 480, and 960mg/Kg body weight. Observations of mice were carried out for 24 hours by observing the number of dead animals and seeing toxic symptoms, body weight, and ROW (Relative Organ Weight) then the data were analyzed statistically. The results showed that the dose of 960 mg caused the most death with LD50 values of 776.2mg and 794.3mg of toxic symptoms, weight loss in mice, and an effect on ROW. This compound can cause death in male and female mice, with the LD50 value of male mice being 776.2mg/kg body weight and female mice at 794.3mg/ kg body weight, and this compound is categorized as slightly toxic.